PENGEMBANGAN MEDIA PEMBELAJARAN PRAKTIKUM FISIKA BERBASIS LINGKUNGAN GUNA PENINGKATAN HASIL BELAJAR SISWADI SMA NEGERI 1 MUARA SUGIHAN KABUPATEN BANYUASIN - Rosdiana . (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
This research aims to produce environment-based learning media for physic practicum which is valid, practical, and effective, in order to improve student learning outcomes on the Senior High School 1 Muara Sugihan in Banyuasin Regency. This research is research and developments, with the respondents of this research are students from the Class of X.2 on that school. The environment-based learning media for physic practicum consists of teaching material, Practicum Worksheet for Student, and visual teaching aid was developed with Rowntree Model, with to the evaluate steps used Tessmer formative evaluate. Prototype 1, design which are categorized as very valid is expert review and one-to-one evaluation, with the result expert review to teaching material (4.75), practicum worksheet for student (4.86), and visual teaching (4.51), meanwhile the result one-to-one evaluation (4.80). Prototype 2 is practical and the potentially effective design to the result student learning outcomes when during learning activity, this is show the result small group with the average activity learning student (76.25%), activity practicum (psycho-motor) student (66.35%), the all with categorized as good, meanwhile the average participant’s reactions and participant’s learning (4.20) which is very good category, to the result student learning outcomes reach the average value (84.53) which is in high category. Next the two prototypes are revise design which are effective of the result field test of the respondents, the average activity learning student (74.476%), activity practicum (psycho-motor) student (79.12%), the all with categorized as good, meanwhile the average participant’s reactions and participant’s learning (4.075) which is very good category, to the result student learning outcomes reach the average value (76.65) which is in high category, where in details 7 students or 20 % is very high, 12 students or 34.29 % is categorized as high, 10 students or 28.57 % is moderate, and 6 students or 17.74 % is low, while no student or 0 % is in very low category. To the result of questionnaire, responds students are very good, with the average responds on learning media shows value of (83.60%), and the average responds on learning process for physic practicum has value of (89.71%). Thus it can be conclude that the environment-based learning media for physic practicum consisting of teaching material, Practicum Worksheet for Student, and visual teaching aid developed by researcher is valid, practical and effective during learning activity on the subject of optical instruments.